Cumplimiento de los indicadores de calidad en el área de Quirófano del Hospital General Isidro Ayora - Loja - Angamarca Pullaguari, Joana Nathaly (2023)
Quality in health services permits achieving desired results to guarantee patient safety with the implementation of care processes, since failures, deficiencies and errors can often have devastating consequences for users and their families due to injury, damage, illness and death. Therefore, the objective of this study was to evaluate the fulfillment of quality indicators in nursing care in the operating room area at Isidro Ayora Hospital. The type of study was quantitative, descriptive and cross-sectional, using the technique of documents revision in records, medical records and direct observation. A checklist was used for data collection, which was out of two sections, the first one was to know the infrastructure and the personnel working in the service, and the second part of the instrument evaluated the compliance of the safe practices. The results showed that the area is made up of 20 professional nurses, with a majority of personnel in comparison with other professionals. In terms of compliance with safe practices, 100% was obtained, which means that the service reached the maximum standard of compliance, while the assistance practices did not reach the desired standard, due to failures in the application of some practices such as: control of dangerous abbreviations, correct administration of medications and venous thromboembolism prophylaxis, likewise, in the administrative/assistance practices a favorable result was not obtained due to poor adherence to hand hygiene, safe surgical practices, fall prevention, notification of events related to patient safety and correct transfer of patient information at transition points. In conclusion, the operating room service did not reach the maximum standard of compliance in safe practices, so a culture of safety should be promoted in order to reduce the risks to patients and improve the quality of care